2003
DOI: 10.1074/jbc.m209998200
|View full text |Cite
|
Sign up to set email alerts
|

Calcium/Calmodulin-dependent Protein Kinase Activates Serum Response Factor Transcription Activity by Its Dissociation from Histone Deacetylase, HDAC4

Abstract: Serum response factor (SRF) plays a pivotal role in cardiac myocyte development, muscle gene transcription, and hypertrophy. Previously, elevation of intracellular levels of Ca 2؉ was shown to activate SRF function without involving the Ets family of tertiary complex factors through an unknown regulatory mechanism. Here, we tested the hypothesis that the chromatin remodeling enzymes of class II histone deacetylases (HDAC4) regulate SRF activity in a Ca 2؉ -sensitive manner. Expression of HDAC4 profoundly repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(84 citation statements)
references
References 57 publications
4
80
0
Order By: Relevance
“…However, the discovery of a physical clustering, corequirement and sufficiency of the 3 activitydependent cis-regulatory elements located in such close proximity (Ϸ100 bp) in SARE is particularly striking, suggesting that SARE may have a unique role as a coincidence detector for the 3 activity-dependent transcription factors. Intriguingly, we observed that mutations in the SRF-binding site not only abolished SARE activation, but also significantly augmented basal activity under silenced conditions, suggesting an additional role of SRF for transcriptional repression as previously reported in certain contexts in nonneuronal cells (29).…”
Section: Visualization Of Activated Cells In a Neuronal Circuit Usingsupporting
confidence: 87%
“…However, the discovery of a physical clustering, corequirement and sufficiency of the 3 activitydependent cis-regulatory elements located in such close proximity (Ϸ100 bp) in SARE is particularly striking, suggesting that SARE may have a unique role as a coincidence detector for the 3 activity-dependent transcription factors. Intriguingly, we observed that mutations in the SRF-binding site not only abolished SARE activation, but also significantly augmented basal activity under silenced conditions, suggesting an additional role of SRF for transcriptional repression as previously reported in certain contexts in nonneuronal cells (29).…”
Section: Visualization Of Activated Cells In a Neuronal Circuit Usingsupporting
confidence: 87%
“…Indeed, it has been speculated (Lemercier et al, 2002) that recruitment of class II HDACs to repress transcription could be a common mechanism for this family of proteins. Evidence is accumulating that class II HDACs help mediate the transcriptional repression of genes crucial for differentiation, as documented for the serum response factor (SRF) (Davis et al, 2003), MEF-2 in myogenesis McKinsey et al, 2000;Dressel et al, 2001), or GATA-1 in erythroid differentiation (Watamoto et al, 2003), and our results suggest that HDAC4 could play a key role in PLZF-mediated myeloid differentiation. Interestingly, in contrast to MEF-2, PLZF does not seem to interact with the N-terminal region of HDAC4.…”
Section: Discussionsupporting
confidence: 62%
“…As SRF and Etslike transcription factor 1 (Elk1), binding sites for which are present in Region-1, were previously reported to interact with HDACs (24,25), it is possible that Arc transcription is suppressed by HDAC-mediated repressive machinery. Therefore, we examined the effects of trichostatin A (TSA), an inhibitor of HDAC, on Arc expression.…”
Section: Identification Of Bdnf-responsive Elements In Region-1 Of Thmentioning
confidence: 99%